Pengaruh Model Pembelajaran Kooperatif Tipe TGT terhadap Hasil Belajar IPA Peserta Didik Kelas Vii SMPN 1 Mangarabombang Takalar - Yulinar Anshar; Ramlawati Ramlawati; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2024)
This research aims to determine: (1) students' science learning outcomes scores before and after being taught using the TGT type cooperative learning model, (2) students' science learning outcomes scores before and after being taught using the direct learning model, (3) improvement in learning outcomes Science students are taught using the TGT type Cooperative Learning model and classes taught using the direct learning model, (4) the influence of the TGT type cooperative learning model on students' science learning outcomes. This type of research is Quasi Experimental Design research and Pretest-Posttest Non-Equivalent Control Group research design. The sample was selected by purposive sampling and obtained class VII C and class VII D with a total of 33 students each. The research instrument is in the form of learning outcome test questions. Data collection techniques are pretest and posttest. The data were analyzed with descriptive and inferential statistics The research results show that: (1) the students' science learning results before and after being taught using the TGT type cooperative learning model, namely in the pretest, an average score was obtained of 2.84 and the posttest learning result score obtained an average score of 7.07. (2) students' science learning results before and after being taught using the direct learning model, namely in the pretest the average score was 2.47 and the posttest learning results obtained an average score of 4.56. (3) the increase in science learning outcomes for class VII students at SMPN 1 Mangarabombang Takalar who were taught using the TGT type cooperative learning model experienced an increase with an N-Gain result of 0.61 which indicates the medium category. Meanwhile, learning outcomes taught using the direct learning model have increased with an N-Gain result of 0.23 which indicates the low category, (4) there is an influence of the TGT type Cooperative learning model on improving the learning outcomes of class VII students at SMPN 1 Mangarabombang Takalar.